The Effect of Post-Traumatic Stress Disorder on Women After The Earthquake in Central Sulawesi - Andini Rizki Amanda; Atik Choirul Hidajah; Chatarina Umbul Wahyuni (Universitas Airlangga, 2021)
Background: Posttraumatic stress disorder (PTSD) is a psychological disorder caused by uncommon occurrences such as threats or catastrophic events. Women are particularly susceptible to developing PTSD, as they have a range of threat perceptions. Purpose: The aim of this study was to examine the effect of PTSD on women survivor of the earthquake in the Sigi Biromaru sub-district of Central Sulawesi. Methods: This was a descriptive study conducted using a cross-sectional design. The population for this study were housewives who have been displaced by the earthquake and are currently residing in temporary shelters (Huntara) in a village located in the Sigi Biromaru sub-district. The instrument used in this study was the PTSD measurement questionnaire sheet. It was conducted from March to April 2020 and included a total of 115 participants. Univariate analysis was used to determine the respondents’ characteristics, including their age, education, occupation, income, and a description of the PTSD condition. Results: The results show that the majority of respondents experienced severe PTSD (70.43%). Most of the respondents (35.65%) were between the ages of 37 and 46, were senior high school graduates (40%), were unemployed (74%), and had earnings of < 2,500,000 (85.22%). Three variables that affect PTSD are education with a p-value of 0.03 < 0.05, job/occupation with a p-value of 0.02 < 0.05, and income with a p-value of 0.03 < 0.05. Conclusion: Women who are elderly, have a low level of education, are unemployed, and have low income are more vulnerable to experiencing PTSD.